Penerapan Pajak Natura Sebagai Upaya Mencapai Keadilan Sosial Bagi Pekerja Indonesia - Muan Ridhani Panjaitan; Yuna Yuna (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The implementation of PMK 66 Tahun 2023, also known as the Natura tax regulation, has sparked debate. On one hand, some view it as an excessive effort by the state to pursue tax revenue. On the other hand, others see it as the state's endeavor to achieve collective well-being. This study analyzes the 2023 PMK 66 based on the theory of hierarchical legal norms (Stufenbau) to understand the alignment of PMK with the overarching legal standards, particularly Indonesia's foundational philosophy, Pancasila. Ultimately, the goal is to achieve social justice for all Indonesian citizens, primarily through the fair application of tax policies that prevent practices such as money laundering and other forms of tax fraud.